Metodologia de educação ambiental com utilização da tecnologia Oásis Educar em escola pública (Rio Claro, SP) - Cassanti, Ana Clara [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Social disparity remains in contemporary societies. The socio-economic inequalities are recognized in several indicators, such as housing sites, availability of basic resources like water and sanitation and even the quality of education offered. Environmental education is an educational proposal increasingly discussed and that is extremely important, since leaving young people aware of environmental issues, there will be citizens more aware of the importance of environmental quality for proper human development. Considering that most of our knowledge is acquired within the school environment, it is proposed to carry out theoretical and practical activities made by students multipliers from university. Due to this, the students are aware of the major environmental problems that impact the daily life of cities. The activities were carried out based on a social technology from Elos Institute called Game Oasis which seeks to integrate the school with the community that makes up in order to perform a cooperative real change that is a common dream of the community/school with focus on environmental changes. These activities were conducted focusing on the work with values to young people in different meetings and after that, they will develop the physical change in their community/school. The activities took place in a public school in the city of Rio Claro, State School Teacher Odilon Correa. To evaluate the young people who participated in the activities, it was applied pre and post tests that verified the knowledge of young people in relation to environmental issues and also the question of values. Thus, the objective of the project is to verify that awareness is possible on the environmental issue of young people using as a methodology based on the social technology Game Oasis, modified for environmental education in school. It is believed that with the work with... (Complete abstract electronic acess below)

A disparidade social permanece nas sociedades contemporâneas. As desigualdades sócioeconômicas são reconhecidas em diversos indicadores, como: locais de habitação, disponibilidade de recursos básicos como água e esgoto e até mesmo a qualidade da educação oferecida. A educação ambiental é uma proposta educacional cada vez mais discutida e que apresenta grande importância, uma vez que deixando os jovens conscientes das questões ambientais, haverá a formação cidadãos muito mais conscientes da importância da qualidade ambiental para o adequado desenvolvimento humano. Levando em consideração que a maioria de nossos conhecimentos são adquiridos dentro do ambiente escolar, tem-se como proposta a realização de atividades teóricas e práticas feitas por alunos de universidade multiplicadores do tema, para que todos os alunos se conscientizem sobre os grandes problemas ambientais que impactam o cotidiano das cidades. As atividades foram realizadas tomando como base com uma tecnologia social do Instituto Elos chamada Jogo Oásis a qual busca a integração da escola com a comunidade que a compõe de forma a realizar de maneira cooperativa uma mudança real que seja um sonho em comum da comunidade escolar com enfoque em mudanças ambientais. Estas atividades foram realizadas focando em trabalho de valores aos jovens em diferentes encontros e após isso, eles desenvolveram a mudança física em sua comunidade/escola. As atividades foram realizadas em uma escola pública da cidade de Rio Claro, Escola Estadual Odilon Correa Professor. Para avaliação dos jovens que participaram das atividades, foi aplicado pré e pós testes que verificaram o conhecimento dos jovens em relação à temática ambiental e também à questão de valores. Dessa maneira, o objetivo do projeto é verificar se é possível a conscientização... (Resumo completo,clicar acesso eletrônico abaixo)
Keywords: Educação ambiental; Tecnologia educacional; Meio ambiente; Educação do adolescente; Valores; Rio Claro (SP)